Why should I save energy? - Green, Jen.; Gordon, Mike (London : Wayland, 2008)
A power outage gives Robert the opportunity he needs to teach his friend and her family about the limited sources of energy, what would happen if energy supplies ran out, and some of the ways in which they can all help conserve energy.
Includes bibliographical references (p. 31-32).
3.2
K-3
Keywords: Energy development -- Juvenile literature; Renewable energy sources -- Juvenile literature; Energy development; Energy development